France's foreign and security policy under president Macron: The consequences for Franco-German cooperation - Ronja Kempin (Stiftung Wissenschaft und Politik (SWP), 2021)
French President Emmanuel Macron has announced his goal of revitalising Franco-German relations and founding a 'new partnership' between Paris and Berlin. However, in foreign and security policy, and in certain areas of his Europe policy, this aspiration has rarely been fulfilled. The main reasons are structural changes in international relations, which the French and German sides have reacted to differently. Paris is looking for new ways of preserving its autonomy in defence policy and of filling the strategic vacuum that has been created by the waning US interest in Europe and its periphery. Berlin emphasises the development of NATO and the EU as fundamental organisations for German foreign policy. Reconciling bilateral interests is also complicated by national solo efforts, indifference, and inadequate exchange of experience. The first precondition for intensifying bilateral cooperation is for Paris and Berlin to conduct a comprehensive review of the international conflict situation in their existing cooperation formats as regards foreign and security policy. The two governments need to discuss openly to what extent their national interests are concerned, and then determine concrete measures. Second, they must refrain from national solo efforts and be sensitive to the other's pressure points in foreign, security and Europe policy. The Franco-German Parliamentary Assembly needs to urge the executive of both countries to fulfil the Élysée Treaty and the Aachen Treaty. The findings presented here will be complemented by case studies on Libya, the Common Security and Defence Policy, the Economic and Monetary Union, Russia, NATO, and Turkey.
Keywords: 320